2008
DOI: 10.1093/cercor/bhn073
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Attentional Networks after 1 Night of Sleep Deprivation

Abstract: Here, we assessed the effects of sleep deprivation (SD) on brain activation and performance to a parametric visual attention task. Fourteen healthy subjects underwent functional magnetic resonance imaging of ball-tracking tasks with graded levels of difficulty during rested wakefulness (RW) and after 1 night of SD. Self-reports of sleepiness were significantly higher and cognitive performance significantly lower for all levels of difficulty for SD than for RW. For both the RW and the SD sessions, task difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
136
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(156 citation statements)
references
References 64 publications
13
136
2
Order By: Relevance
“…Chosen value signals in the vmPFC showed a similar attenuation. Reduced lateral and medial parietal cortex responses are frequently observed after SD (Chee and Choo, 2004;Choo et al, 2005;Chee et al, 2006;Lim et al, 2007;Tomasi et al, 2009), and our results extend these observations to parametric value representations. Overall task-related responses (i.e., without parametric modulation) recruited a similar neural system, including the ventral visual stream, lateral PFC, and ACC.…”
Section: Discussionsupporting
confidence: 86%
“…Chosen value signals in the vmPFC showed a similar attenuation. Reduced lateral and medial parietal cortex responses are frequently observed after SD (Chee and Choo, 2004;Choo et al, 2005;Chee et al, 2006;Lim et al, 2007;Tomasi et al, 2009), and our results extend these observations to parametric value representations. Overall task-related responses (i.e., without parametric modulation) recruited a similar neural system, including the ventral visual stream, lateral PFC, and ACC.…”
Section: Discussionsupporting
confidence: 86%
“…2 A, B) and right thalamus (supplemental Table 2, available at www.jneurosci.org as supplemental material). SD-related reduction of task-related parietal cortex activation has been extensively reported (Bell-McGinty et al, 2004;Chee and Chuah, 2007;Tomasi et al, 2009) and is not discussed further in this article.…”
Section: Neuroimaging Findingsmentioning
confidence: 90%
“…Several functional neuroimaging studies have revealed how short-term sleep deprivation (SD) can negatively affect attention Tomasi et al, 2009), working memory (Chee and Choo, 2004;Habeck et al, 2004;Mu et al, 2005), and learning (Drummond et al, 2005;Sterpenich et al, 2009). Yet, it remains unclear whether and how SD shapes the very preferences that guide decision making, independently of these more general effects on cognition.…”
Section: Introductionmentioning
confidence: 99%
“…Even after a single night of partial SD (PSD), alterations of basic attention and more complex cognitive processes can be detected [34,35]. Mostly, these effects are compensable and transient; still, severe cognitive and emotional disturbances may occur if sleep deprivation exceeds a certain limit or persists chronically [36].…”
Section: Introductionmentioning
confidence: 99%